Growth of Land Development Banks in India (International Journal of Innovative Research in Engineering & Management, 2022)
Cooperatives were the first formal  institution to be conceived and developed to purvey credit  to rural India. Indian Economy is largely dependent upon  agriculture as majority of its population is employed in it.  In India, there are 20 State Co-operative agricultural and  rural development banks at apex level and 697 Primary Co operative agricultural and rural development banks at base  level are playing an important role in meeting credit  requirement of rural population in India. The present study  was formulated with the specific objectives to analyze the  growth and performance of Land Development Banks in  India in reference to number of banks, owned funds,  deposits, borrowings, loans and advances, total assets,  profits/losses, non performing assets, ratio of non  performing assets to loans outstanding and ratio of recovery  to demand. The present study is based on secondary data  and it has been collected from the publication of NABARD  and RBI that is, Report on trend and Progress of banking in  India, 2001-02 to 2012– 2012. The data has been collected  for twelve years from 2001-02 to 2011-12. The progress has  been analysed by selecting statistical tools like, mean,  standard deviation, coefficient of variation and exponential  growth rate, trend coefficient, future predication in absolute  and relative terms. From the analysis, it has been observed  that during the study period the performance of land  development banks in India was not satisfactory, State  banks must take necessary steps to improve their performance. The India state co-operative agricultural and  rural development banks are apex banks and they can control and improve the performance of Primary Co operative agricultural and rural development banks under  their vast umbrella.
Keywords: Analysis; Co-operatives; Growth; Performance; Ratios; Recovery